AN UNUSUAL CAUSE OF HYDROPIC GALLBLADDER AND BILIARY COLIC - HETEROTOPIC PANCREATIC TISSUE IN THE CYSTIC DUCT - REPORT OF A CASE AND REVIEW OF THE LITERATURE - (:unkn) unknown (SPRINGER VERLAG, 1993)
We present herein an unusual case of heterotopic pancreas in the cystic duct with hydrops of the gallbladder and concomitant chronic pancreatitis of the heterotopic tissue. A review of the relevant literature is discussed following the presentation of this case.
Keywords: HETEROTOPIC PANCREAS; HYDROPS OF GALLBLADDER; CYSTIC DUCT; PATHOLOGY